The Nature of Human Beings in Islamic Perspective A Philosophical Analysis of Djumransyah’s Thought and Its Implications for Islamic Education - Achmad A’la Derajat; Edi Supriyadi; Farhan (Penerbit Hellow Pustaka, 2026)
This article explores in depth the concept of the essence of human beings in Islamic perspective as formulated by Djumransyah, a modern Indonesian Islamic education thinker. The study highlights the dimensions of humans as physical and spiritual beings, both individual and social, endowed with innate religiosity (fitrah), and entrusted with the responsibility as God’s vicegerent (khalifah) on earth. Using a descriptive-analytical approach based on literature review, this research finds that Djumransyah developed a holistic paradigm of Islamic education rooted in the Qur’an and Sunnah while remaining responsive to contemporary challenges. The findings emphasize the importance of an Islamic education system that fosters balanced human development spiritual, intellectual, moral, and social in order to achieve insan kamil as the ultimate goal of Islamic education.